CT-guided radiofrequency ablation of osteoid osteoma using a multi-tined expandable electrode system - Costanzo, Alessandro; Sandri, Andrea; Regis, Dario; Trivellin, Giacomo; Pierantoni, Silvia; Samaila, Elena; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Radiofrequency ablation (RFA) is the gold standard for the treatment of symptomatic osteoid osteoma (OO) as RFA yields both a high success and low complication rate. It has been widely utilized over the years, but recurrences of OO after this treatment have been documented. These recurrences may be the result of various factors, including incomplete tumor ablation, and are significantly higher in lesions greater than 10 mm. Thus, the need to induce thermal ablation in a wider area led us to use a Multi-Tined Expandable Electrode System (MTEES). In this study we examined the efficacy and safety of RFA using a MTEES in symptomatic OO. Methods: Between January 2005 and June 2007, 16 patients with symptomatic OO were treated by CT-guided percutaneous RFA using a MTEES. The diameter of OO ranged from 6 to 15 mm (mean 10±2.6 mm). Patients were evaluated for clinical outcomes, complications and recurrence. Pain evaluation was assessed preoperatively, 2 weeks postoperatively and at last follow-up. Results: Clinical follow-up was available for all patients at a mean of 84.3 months (range 73-96 months). Mean preoperative VAS score was 7.4 (range 5-9), two weeks after the procedure mean VAS score was 0.3 (range 0-1) with a mean change of -7.06 points (p